How Does Cultural Upbringing Influence How University Students in the Middle East Utilize ChatGPT Technology? - Aad, Samar (2024)
The Middle East, with its diverse cultures and adherence to social norms, offers a relevant case study for exploring the current research question. Using established theories of social interaction and technology acceptance, this research examines how cultural background shapes student interactions with ChatGPT. Analyzing data from 202 online surveys, our findings underscore the gender-based disparities in ChatGPT use, potentially revealing consequences for technology adoption within the Middle East. This study contributes to a deeper understanding of how cultural upbringing influences AI utilization and paves the way for developing more culturally sensitive and inclusive AI systems. By promoting a more equitable and informed approach to AI adoption in the Middle East and beyond, this research offers valuable insights for future research directions and technology applications.